Pengaruh Pembelajaran Online Terhadap Kemandirian Belajar Siswa Kelas II SD Muhammadiyah 17 Surabaya di Tengah Pandemi Covid-19 - Aden Fani Rahmasari; Setiawan, Fajar; Meirza Nanda Faradita (Universitas PGRI Adi Buana Surabaya, 2020)
The COVID-19 pandemic is the first health crisis in the entire world, especially attacking the immunity of everyone so that it becomes a scourge for every community whose activities are mostly carried out at home due to the pandemic. This COVID-19 outbreak has hit 215 countries in the world and has given its own challenges for educational institutions, both from elementary schools, high schools and in Universities. The cause of the COVID-19 outbreak, making all activities starting from school, work had to be temporarily closed to break the chain of COVID-19 distribution. COVID-19 is a virus that attacks human respiration (Ministry of Health, 2020). The purpose of this study was to obtain information related to the COVID-19 pandemic on the effect of student learning at SD Muhammadiyah 17 Surabaya. There are doing online learning that are currently being don such as improving student memory, providing broad insight into their experiences through text, video and audio. Not only that, parents are more often monitoring their children being left behind.